Uyghur social relationships in legal narratives from Republican Xinjiang: Faḍil Shangye in the Kucha documents (1934-1949). Issue 1 (2nd January 2021) - Mirsultan, Aysima
ABSTRACT: Based on a close reading of five legal documents from Kucha, this paper explores judicial practice in Xinjiang in the Republican era. The documents all relate to members of the same family and open a window on to property transactions, family structure and local political administration at the lowest levels of government, across a long enough period to show change over time. Touching upon diverse social practices such as inheritance, the sale of land and making a pledge, the documents demonstrate the mutual integration of Islamic and state law, simultaneously revealing strategies to narrate and constitute social relationships.